Transylvania in the second half of the thirteenth century : the rise of the congregational system - Sălăgean, Tudor, 1968- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2016)
In Transylvania in the Second Half of the Thirteenth Century Tudor Salagean describes the deep transformations of a country that was the scene of a fierce resistance against the great Mongol invasion of 1241-1242. In the second half of the thirteenth century, with the rise of the provincial nobility, Transylvania redefines its internal political system, which reached its maturity during the rule of Ladislas Kan (1294-1315). The appearance of a complex congregational system, also achieved in this period, is connected with the assertion of Regnum Transilvanum , which represents a historical link between the early medieval regnum Erdewel of duke Gyula and the regnum transsilvaniensis of the Union of 1459, announcing the rise of the early modern Principality of Transylvania.